Meningkatkan Kecerdasan Interpersonal Anak Melalui Bermain Ular Naga Pada Kelompok B RA Cerdas Ceria Banyuanyar, Banjarsari, Surakarta Tahun 2014/2015 - Indriyanti Ayuningtias, Melisa, Dra.Surtikandi, SH., M.Pd (2016)
Abstract IMPROVING STUDENTS' INTERPERSONAL INTELLIGENT BY PLAYING DRAGON-SNAKE IN GROUP B OF CERDAS CERIA KINDERGARTEN BANYUANYAR, BANJARSARI, SURAKARTA 2014/2015 ACADEMIC YEAR. This research is Classroom Action Research which aims to know the implementation of playing Dragon-Snake in improving the interpersonal intelligent of the students in Cerdas Ceria kindergarten Banyuanyar, Banjarsari, Surakarta 2014/2015 Academic Year. The subjects of this research are teachers and students group B which totally amounts 34 students. Type of this research is classroom action research which is done in two cycles. The procedure of this research consists of four steps, those are: action planning, implementation, observation, and reflection. The methods are used in collecting the data are interview, notefield, and documentation. Analysis the data of interpersonal intelligent is done by the comparative analysis which means comparing the average of the students' independence with indicator performance in each cycle. Analysis the data of learning by playing Dragon-Snake is done by interactive analysis. The average of students' interpersonal intelligent before investigation is 39, 15%, after the first cycle the students' interpersonal intelligent increases to 56, 53%, and after the second cycle the students' interpersonal intelligent increases to 77, 39%. It can be concluded that learning activity by playing Dragon-Snake can increase the interpersonal intelligent of the student in group B of Cerdas Ceria kindergarten Banyuanyar, Banjarsari, Surakarta 2014/2015 Academic Year. Keywords : intelligent, interpersonal, playing, dragon-snake